Flood Control Capacity of Shenzhen River Basin during "9·7" Torrential Rainfall - ZHOU Hui; LIU Jing; GAO Shiyou; WU Yao; LU Chen (Renmin Zhujiang)
To evaluate whether the current flood control capacity of the Shenzhen River Basin meets design standards, a one-dimensional hydrodynamic mathematical model was employed to simulate the flood process during "9·7" torrential rainfall. Additionally, simulations were conducted to analyze the flood control capacity of the basin under different topographies and roughness conditions. The simulation results indicate that the dredging projects carried out between 2016 and 2020 have enhanced the flood control capacity of the main stream of the Shenzhen River from less than a 20-year return period in some sections to a 50-year return period overall. However, rapid sedimentation and vegetation growth in the riverbed after dredging increase roughness, preventing the upstream section of the Liantang River tributary from meeting the 50-year flood control standard. Currently, the Shenzhen River faces unfavorable underlying conditions, including a fan-shaped catchment topography combined with urban development, significant sedimentation following dredging, and continuous expansion of mangroves at the river mouth, as well as challenges such as frequent extreme weather events and significant urban waterlogging risks. Therefore, to enhance flood control capacity, it is necessary to develop a comprehensive strategy from a basin-wide perspective. A combination of measures including storage, retention, diversion, discharge, and blocking can be used to further reduce peak flood discharges and increase river flood conveyance capacity.